Use of Montessori Education for Therapeutic Purposes in Individuals with Special Needs - Safiye Sunay Yildirim Doğru; Hatice Bilge Doğru (Hryhorii Skovoroda University in Pereiaslav, 2024)
Introductıon. The main idea of Montessori Pedagogy and Montessori Therapy based on it is to contribute to the development of the child by accepting them with their own personality and providing special 'sensory development tools' and activities suitable for the child's 'structure plan'. Purpose. This study will focus on the therapeutic use of the Montessori method in infants and young children with special needs. Also, it is aimed to explain Montessori Therapy and its usage in the education of children with special needs in-depth and to evaluate the perspectives of parents of children with special needs on Montessori Therapy.Method. The research is a descriptive study and includes compiling information on Montessori therapy and the results of interviews conducted with the families of five children with special needs. The research data consists of a literature review and family interviews. Results. As a result of the research, parents of children with special needs stated that alternative preschool education (Montessori education) approaches for their children could be effective in helping children acquire basic life skills.Conclusion. Montessori principles such as individualized learning, manipulative materials, freedom and discipline, natural environment, and continuous observation can help maximize the potential of these children. However, every child is unique, and the therapy may need to be constantly adapted to be effective. Therefore, practitioners of Montessori therapy should carefully observe and assess the needs of the children, and continuously update themselves with current research and best practices.